A technology to improve the formability of thin-walled aluminum alloy corrugated sheet components using hydroforming. Issue 1 (April 2016) - Kong, Deshuai; Lang, Lihui; Sun, Zhiying; Ruan, Shangwen; Gu, Shanshan
Abstract The explosively forming projectile (EFP) has been traditionally adopted for the manufacturing of aluminum thin-walled corrugated sheet. These components have large deformation ranges but inferior formability. Additionally, the process usually delivers inferior surface quality with long manufacturing cycle time and high cost. The active hydroforming process is suggested to solve these issues during EFP. A new technology named as blank bulging by turning the upside down active hydroforming technology is proposed to overcome problems like nonuniform thickness distribution and cracking failure of corrugated sheet during the conventional hydroforming process. FEM simulations and experiments were conducted to validate this new technology. The effects of strain rate on the formability of aluminum alloy AA2024-O during the active hydroforming process were investigated according to the bulging test with pressure rate control. Results indicate that aluminum alloy AA2024-O is not sensitive to pressure rate (strain rate) at room temperature. Furthermore, the deformation capacity of aluminum alloys can be improved effectively, and more uniform distribution of wall thickness can be obtained by this new method. It can be concluded that the new method is universal for thin-walled, shallow drawing parts having complex sections.